1999
DOI: 10.1002/(sici)1522-2683(19990701)20:10<2086::aid-elps2086>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes in myocardial protein expression in pacing-induced canine heart failure

Abstract: Canine rapid ventricular pacing produces a low output cardiomyopathic state which is similar to dilated cardiomyopathy. In this study dogs were paced at 245 beats per minute (bpm) for 3±4 weeks until signs of heart failure were apparent. Unpaced dogs were used as controls. A previous study identified myocardial protein changes in the pH region 4±7 following ventricular pacing by using two-dimensional electrophoresis (2-DE) (Heinke et al., Electrophoresis 1998. Many of these proteins were associated with mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 5 publications
3
12
0
Order By: Relevance
“…Despite the diversity in the pathogenesis of heart failure, defects in energy metabolism have been implicated in the disease progression (Ingwall 1993; Dzeja et al 2000; Lehman & Kelly, 2002; Ventura‐Clapier et al 2002). Proteomic analysis has shown that many of the cardiac proteins altered in CHF are involved in energy metabolism (Heinke et al 1999). Marked reductions in the complexes of the respiratory chain have been described in both cardiac and skeletal muscles in canine and rat heart failure models (Ide et al 2001; Marin‐Garcia et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the diversity in the pathogenesis of heart failure, defects in energy metabolism have been implicated in the disease progression (Ingwall 1993; Dzeja et al 2000; Lehman & Kelly, 2002; Ventura‐Clapier et al 2002). Proteomic analysis has shown that many of the cardiac proteins altered in CHF are involved in energy metabolism (Heinke et al 1999). Marked reductions in the complexes of the respiratory chain have been described in both cardiac and skeletal muscles in canine and rat heart failure models (Ide et al 2001; Marin‐Garcia et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…52 Reduced tubulin mRNA and free and polymerized tubulin levels have been observed in dogs with tachycardia-induced cardiomyopathy. 53 Heinke et al 54 stimulated canine hearts at 245 bpm for 4 weeks and then at 190 bpm, and studied protein patterns of LV from the paced myocardium with controls. Elongation factor Tu was present only in the control hearts.…”
Section: Abnormalities In Excitation-contractionmentioning
confidence: 99%
“…The conducted tests correspond to intergroup comparisons with 1024 × 1024 8-bit images, and 2D protein separation patterns were visualized by silver staining using standard protocols [48] and [49].…”
Section: Methodsmentioning
confidence: 99%